Information Asymmetry and Voluntary SFAS 157 Fair Value Disclosures by Bank Holding Companies During the 2007 Financial Crisis1. (September 2017) - Weiss, Renee; Shon, John
Abstract: We hand‐collect SFAS 157 voluntary fair value disclosures of 18 bank holding companies. The SEC's Division of Corporate Finance likely targeted these entities in 2008 through their "Dear CFO" letters in which they requested specific, additional disclosure items. We collect disclosures that match the SEC recommendations and create eight common factor disclosure variables to examine the effect of such disclosures on information asymmetry. We find that disclosure variables about the use of broker quotes or prices from pricing services and the use of market indices and illiquidity adjustments are related to lower information asymmetry. However, disclosure variables about valuation techniques and asset‐backed securities are related to greater information asymmetry. We also document that disclosure complexity, and disclosure tone (uncertainty and litigious) is related to greater information asymmetry. These findings are consistent with criticism that corporate disclosures are voluminous; management may obfuscate unfavorable information which in turn increases market participants' assessment of uncertainty associated with the fair value measures. We caveat that the setting of the financial crisis and a small sample size may limit the ability to generalize these inferences to other time periods or other financial firms.